PENDAMPINGAN CERDAS BERMEDIA SOSIAL PADA ORANGTUA SISWA SD MUHAMMADIYAH LAWANG - Tutik Sulistyowati; Luluk Dwi Kumalasari; Mochamad Aan Sugiharto (JPM PAMBUDI, 2020)
The development of communication technology, especially mobile phones (HP), demands the role of parents in being able to assist children in using it. Elementary school’s children nowadays are easy to open and use all the features available, so they have become accustomed to using social media. The tendency of children in social media still needs parental supervision and control, but not all parents are able to compensate for the intelligence of children in using mobile phones and existing features, especially Social Media. Therefore, efforts are needed to educate parents in assisting children in communicating through technology. This dedication is done in an effort to educate students' parents accompanying their sons to be smart in social media at Muhammadiyah Lawang Elementary School.